Analisis Kebutuhan Ruang Bagi Siswa Berkebutuhan Khusus di Sekolah Luar Biasa Melalui Pendekatan Studi Perilaku - Huda Asyifa Putri; Yonav Partana; Lia Rosmala Schiffer (Fakultas Teknik - Universitas Bung Karno, 2024)
Special schools provide educational services for students with special needs, where the design of physical spaces plays a crucial role in creating an inclusive learning environment. This study aims to understand the spatial requirements based on the characteristics of students with special needs through the behavioral approach in architecture. The research employs a qualitative method with source triangulation techniques to analyze data, revealing that spatial needs in special schools differ significantly from those in regular schools. Necessary adjustments include the selection of furniture, visual learning media, and specialized learning spaces such as self-development and communication rooms to support students' growth. By aligning with educational regulations, special schools can create an optimal learning environment, enabling students to access learning materials more effectively and develop their full potential.